(3GdJYbjHGJ Ydi GdehVhYGJs - (3CHhHcQ Hf eMeO GdSjhWjs; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3hHYO aEf cJGH GdehVhYGJ LeY GdEeGe Hf GdLhRj bO fHg GdMGaX bOjekG hMOjKkG Ydi Cf ajg JSGgdkG cHjQkG Ch CMGOjK djSJ HehVhYg s
(3BNQgG (B:s
(3heG CNQL GdSfj hHf NRjeg eY GdHjgbj hGdOGQbWfj Ke GdcJGH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1906s
Keywords: (3GdMOjK h GdeUWdMs